Normality Criteria of Meromorphic Functions Concerning Shared Analytic Function (Communications in Mathematical Research, 2021)
In this paper, we use Pang-Zalcman lemma to investigate the normalfamily of meromorphic functions concerning shared analytic function, which improvessome earlier related results.